Evaluation of a tablet-based instruction of breathing technique in patients with COPD. (October 2016) - Chan, Hui-Ya; Dai, Yu-Tzu; Hou, I-Ching
Highlights: Tablet -based instruction might be a supplement to enhance elderly patients to learn through elevating their self-efficacy. The effect on self-efficacy did not last even if patients are assisted by our tablet computer application. More comprehensive interventions or "booster" lessons may be needed to maintain high self-efficacy. Further research to clarify the best style of tablet computer-aided learning in older populations is needed. Abstract: Purpose: Tablet computers are a convenient audio-visual aid for patient education. Teaching patients with chronic obstructive pulmonary disorder (COPD) appropriate therapeutic breathing techniques and encouraging them to practice regularly has been recognized as an effective care strategy. The purpose of this study was to evaluate the effectiveness of using a tablet computer with the Breathing Easier Support Toolkit (BEST), a supplemental software application we developed that instructs and assists COPD patients during the process of respiratory retraining. Patients and methods: From May 2013 to September 2014, participants were randomly assigned to an experimental group (n = 36) or a control group (n = 35). Correct breathing technique, practice frequency, application of breathing technique, self-efficacy, quality of life, and patient feedback on the tablet-computer education were evaluated with blinded assessments at baseline and immediate, 1-month, and 3-month follow-up assessments after training completion. Data analysis consisted of basic characteristics and outcome indicators presented in terms of descriptive statistics; inferential statistics were estimated by generalized estimating equations. Results: The participants were mostly male (83.1%) with an average age of 71.5 (SD = 11.4). Both the experimental and control groups showed statistically significant improvement in correct breathing technique and application of breathing technique from baseline for each follow-up ( p  < 0.001). A significantly increase in self-efficacy for the experimental group was found immediately after completing the breathing retraining program compared to the control group ( p  = 0.045). Conclusion: Our tablet computer-assisted educational aid did not provide an improvement over the traditional method for teaching breathing techniques to elderly patients with COPD. The results only showed an immediate effect on the self-efficacy of the breathing technique. The elderly did not use the tablet computer actively and the research was conducted without intervention after discharge, which may be a reason why the effect did not last. Further research to evaluate the effectiveness of such a strategy for the elderly is needed in the future.